Curriculum enhancement through co-creation: Fostering student-educator partnerships in higher education - Cabral, Ana; Fuller, Stephanie; De Wilde, Janet; Khama, Khahliso; Melsen, Marianne (International Journal for Students as Partners, 2023)
This case study presents an institutional approach to curriculum enhancement and co-creation. It explores how these two elements of a university’s strategy interlink through institutional values, curriculum development initiatives, and the advent of a new recognition scheme for student co-creators at Queen Mary University of London in the UK. It explores how the delivery of curriculum enhancement projects has been made possible through co-creation with students and discusses its outcomes: curriculum enhancement resources for staff and students, recognition for students, and joint presentations and publications. This case study also reflects on the experience of student co-creators and the benefits and challenges for staff and the institution, considers the specific contexts required to promote a shift in institutional culture towards co-creation, and shares successes and recommendations for implementing this approach.